ANALYSIS OF ERROR USE OF PHRASES IN PRIVATE HIGH SCHOOL STUDENTS OF ISLAM IN YARANG REGION, PATTANI REGION, SOUTH THAI - Jehwae, Phaosan; Deliani , Susy; Harahap, Muhammad Haekal (LUMBUNG AKSARA, 2022)
This research aims to identify the misuse of non-standard Malay Standard (BMS) phrases among private religious school students (pondok schools), yarang district, Pattani Region, Pattani Region. This research is deemed necessary because the status of Standard Malay in the education system in Thailand even in the Patani (South Thai), the majority of Malays, the Malay language status far below the status of Thai language. The findings of the research show five types of phrase-use mistakes, mistakes for using (i) phrases that use foreign words, (ii) phrases whose structure violates the Malay phrase structure, (iii) phrases that represent omission, Which is incompatible with Malay words, and (v) phrases that illustrate Malay grammar errors.